2013
DOI: 10.1016/j.ibmb.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Bt maize in Mythimna unipuncta (Lepidoptera: Noctuidae) is mediated by alteration in Cry1Ab protein activation

Abstract: Bt maize cultivars based on the event MON810 (expressing Cry1Ab) have shown high efficacy for controlling corn borers. However, their efficiency for controlling some secondary lepidopteran pests such as Mythimna unipuncta has been questioned, raising concerns about potential outbreaks and its economic consequences. We have selected a resistant strain (MR) of M. unipuncta, which is capable of completing its life cycle on Bt maize and displays a similar performance when feeding on both Bt and non-Bt maize. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…For example, the lack of a protease activating Cry1Ac protoxin is linked with resistance in Plodia interpunctella and Helicoverpa armigera . Furthermore, decreased protoxin activation is implicated in resistance to Cry1Ac in Plutella xylostella , and to Cry1Ab in Ostrinia nubilalis , Heliothis virescens and Mythimna unipuncta …”
Section: Introductionmentioning
confidence: 99%
“…For example, the lack of a protease activating Cry1Ac protoxin is linked with resistance in Plodia interpunctella and Helicoverpa armigera . Furthermore, decreased protoxin activation is implicated in resistance to Cry1Ac in Plutella xylostella , and to Cry1Ab in Ostrinia nubilalis , Heliothis virescens and Mythimna unipuncta …”
Section: Introductionmentioning
confidence: 99%
“…An estimated 0.1 million hectares of Bt -corn were grown in Spain in 2014 (James, 2014). However, recent studies have reported a reduced efficacy of Bt transgenes as some important pests have developed resistance to them (Campagne et al, 2013; Gonzalez-Cabrera et al, 2013). Insect resistance is the main risk for the success of this control tool (McGaughey and Whalon, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The low efficacy of Bt maize hybrids expressing the Cry1Ab toxin against M. unipuncta has raised concerns about the consequences that Bt maize deployment could have on the assemblage of the lepidopteran community in maize fields . Larvae of M. unipuncta can feed from neonates on Cry1Ab‐expressing maize plants, and about 1–2% are capable of completing their life cycle . The high rates of toxin elimination and the rapid recovery of the midgut epithelium after Bt toxin ingestion are probably involved in the basal tolerance of this species to the Cry1Ab toxin .…”
Section: Introductionmentioning
confidence: 99%
“…This situation represents a scenario of non‐compliance with the ‘high‐dose’ strategy for this species. Although outbreaks of M. unipuncta have not been reported in Bt maize fields, the populations of this secondary pest are exposed to high selection pressure in hotspot areas (high adoption rate and repeated cultivation of Bt maize) in the Ebro Valley (north‐east Spain), where the risk of field‐evolved resistance increases . Indeed, we have demonstrated that a laboratory‐selected MON810‐resistant (MR) strain of M. unipuncta was able to develop resistance to MON810 maize after 5–12 generations of laboratory selection (22–57% of the larvae completed their life cycle on Bt maize plants), this resistance being mediated by the alteration of toxin activation by midgut proteases …”
Section: Introductionmentioning
confidence: 99%